Preparation and characteristics of multiple emulsions containing liquid crystals. Issue 8 (21st June 2018) - Zhang, Wan-Ping; Li, Ling-Yu; Jia, Bing; Ou, Wen-Hua; Song, Li-Li; Zhang, Qian-Jie
ABSTRACT: In this paper, multiple emulsions containing liquid crystals were prepared successfully and the influence of formulation parameters on the formation mechanism was studied. Moreover, differential scanning calorimetry (DSC), small-angle X-ray scattering (SAXS) spectra analysis and stability analysis were used to characterise the property of them. The results showed that the chemical structure of water-in-oil (W/O) emulsifiers directly impacted on the formation of multiple structure, but the effect on the formation of liquid crystal structure was negligible. With the gap of the polarity between inner and outer liquid oils decreased, both multiple structure and liquid crystal structure were harder to form. The content of sodium chloride in internal aqueous phase, which should be neither too high nor too low, has great impact on the formulation of multiple structure. It was easier to form two structures simultaneously when the carbon chain length of fatty alcohols was closer to that of emulsifier C22 alkyl polyglucoside (202). DSC elucidated the phase transitions of water in the liquid crystal layer and the W/O emulsions. SAXS indicated that the liquid crystal orientation was lamellar. The stability analysis showed that the presence of liquid crystal structure had a significant contribution to the stability of the multiple emulsions. GRAPHICAL ABSTRACT: